Analisis Usahatani Kentang (Solanum Tuberosum L.) Di Berbagai Pola Tanam (Studi Kasus Desa Sumber Berantas Batu) - Arifitus Balto Jedhe (Fakultas Pertanian, 2021)
In the management of a farm, farmers seek to terms obtained economically profitable, where costs can generate maximum production. So in the end farmers' income increase, with rising incomes then off automatically farme welfare level will increase. According Purba (2008), the cropping pattern is a sequence of planting on a plot of land in one year, including soil treatment period. Implementation of the cropping pattern of a technical irrigation area in a year, usually carried out by the Decree of the Head of the Local. Besides the considerations in support of national food policy, the determination of the cropping pattern is also made based on the availability of water and aspirations of farmers.